Optimisation of spray drying process conditions for sugar nanoporous microparticles (NPMPs) intended for inhalation - CORRIGAN, OWEN; HEALY, ANNE; TAJBER, LIDIA; AMARO, MARIA INES (My University, 2011)
The present study investigated the effect of operating parameters of a laboratory spray dryer on powder characteristics, in order to optimise the production of trehalose and raffinose powders, intended to be used as carriers of biomolecules for inhalation. The sugars were spray dried from 80:20 methanol:n-butyl acetate (v/v) solutions using a buchi mini spray dryer b-290. A 24 factorial design of experiment (doe) was undertaken. Process parameters studied were inlet temperature, gas flow rate, feed solution flow rate (pump setting) and feed concentration. Resulting powders where characterised in terms of yield, particle size (ps), residual solvent content (rsc) and outlet temperature. An additional outcome evaluated was the specific surface area (ssa) (by bet gas adsorption), and a relation between ssa and the in vitro deposition of the sugar npmps powders was also investigated. The doe resulted in well fitted models. The most significant factors affecting the characteristics of the npmps prepared, at a 95% confidence interval, were gas flow: yield, ps and ssa; pump setting: yield; inlet temperature: rsc. Raffinose npmps presented better characteristics than trehalose npmps in terms of their use for inhalation, since particles with larger surface area resulting in higher fine particle fraction can be produced.
PUBLISHED
Keywords: Pharmacology; Factorial Design; Raffinose; Trehalose